Avaliação comparativa da analgesia preemptiva do ibuprofeno e etoricoxibe em cirurgia de terceiros molares : um ensaio clínico randomizado, duplo-cego, placebo-controlado, cruzado - Costa, Fabio Wildson Gurgel (2013)
Third molar surgery is a frequent procedure in dentistry related to variable degrees of postoperative pain. In this context, non-steroidal anti-inflammatory drugs have been commonly used in studies that evaluated the efficacy of preemptive analgesia as a strategy for pain control. Thus, the aim of the present study was to evaluate the preemptive analgesic efficacy and anti-inflammatory effect of ibuprofen and etoricoxib in mandibular third molar surgery, compared with a placebo. A randomized, double-blind, placebo-controlled crossover trial was conducted with patients undergoing a surgical removal of mandibular third molars with similar pattern of bone inclusion and surgical difficult between right and left sides, requiring bone removal under local anesthesia. Eighteen eligible patients were allocated into three groups to receive 1 hour preoperatively a single dose of ibuprofen 400 mg, etoricoxib 120 mg, or placebo. Pain intensity, use of analgesic rescue medication, swelling and maximum mouth opening were evaluated. The overall median (minimum - maximum) of pain scores was different between groups (p < 0.0001): ibuprofen, 0.0 (0.0 – 5.5); etoricoxib, 0.0 (0.0 – 3.5); placebo, 1.0 (0.0 – 7.0). Etoricoxib reduced pain scores significantly in comparison with ibuprofen (p < 0.05). The pain score peak occurred 6 hours after surgery between 3 compared groups (p < 0.0001). Rescue medication was used in 83.33%, 75%, and 100% of surgical procedures receiving ibuprofen, etoricoxib, and placebo, respectively (p = 0.1967). The mean of consumed rescue medication was different between ibuprofen (1.7±2.0), etoricoxib (0.8±06), and placebo (1.0±2.7) groups over the study period (p = 0.0052), and was significantly lower in etoricoxib group by comparison with the placebo group (p < 0.05). Among study periods, there was no statistically significant difference between groups in relation to median values of facial swelling (p > 0.05) and mean values of maximum mouth opening (p > 0.05). In conclusion, ibuprofen and etoricoxib significantly reduced the intensity of postoperative pain and the need for use of rescue medication compared to placebo group. Etoricoxib showed a better preemptive analgesic activity than ibuprofen. Both drugs did not exert significant anti-inflammatory effect able to reduce swelling and trismus in comparison with placebo group.